Regulação financeira e incentivo ao microcrédito como formas de promoção do desenvolvimento. - Oliveira, Bruno Bastos de (2012)
This dissertation focuses on the need for effective financial regulation as a way of implementing microcredit policies, able to be an important ally in the struggle against poverty and consequent realization of national development project planned by the current constitutional text. It aims to perform a delimitation of this kind of credit, pointing out the situations it can be applied, the benefits for the country, the economic impact and realization of human dignity. For its consummation, the method of deductive approach was used, methods of historical procedure, comparative, interpretive and analytical techniques as well as bibliographical and documentary research. Fulfilling all the objectives established, describes the regulation of markets and, in particular, the financial system, pointing out the reasons of a effective regulation. Makes the relationship between financial regulation and national development, emphasizing the need to reach social purposes by the institutions that compose this system, and microcredit been a prominence politics. Certifies the conclusion that the incentive to microcredit as social policy is essential and must not only be implemented by the public sector, acquiring aspects of public policy, but also by the private sector, requiring, in consequence a kind of inductive regulation, so that national development can be reach the greatest extent possible.